Revisiting EKC hypothesis through Income Inequality and Environmental Degradation in ASEAN-5 Countries - Agustin, Isnaini Nuzula; Putri, Inda Meyllya; Marheni, Dewi Khornida (Jurnal Economia, 2026)
This study examines the influence of GDP, corruption, financial development and Trade Openness on environmental degradation within the framework of the Environmental Kuznets Curve (EKC) hypothesis in ASEAN-5 emerging countries. Further, this study investigates the mediating role of income inequality. Utilizing panel data from 1990 to 2022 and the Autoregressive Distributed Lag (ARDL) approach, the findings found support the existence of a U-shaped EKC hypothesis, implying that while economic growth initially degrades environmental quality, it ultimately leads to improvements at higher income levels. The results noted that corruption exacerbates income inequality while trade openness and financial development affect income inequality in the long run. Additionally, the results posit the role of income inequality as a mediator. The results highlight the importance of implementing policies aimed at reducing corruption and income inequality to enhance environmental outcomes thus providing crucial insights for policymakers seeking to balance economic development with environmental sustainability.